A triboelectric nanogenerator based on white sugar for self-powered humidity sensor. (December 2020) - Liu, Hongye; Wang, Hao; Fan, Yanping; Lyu, Yan; Liu, Zenghua
Highlights: A novel TENG based on white sugar to harvest mechanical energy was reported. White sugar as food material of edible is first used as the triboelectric material. The peak output of Isc and Voc can reach 6.35 μA and 95.68 V for the WS-TENG. The proposed device realizes the integration of power supply and humidity sensing. Abstract: The triboelectric nanogenerator (TENG) based on the contact-electrification and electrostatic induction are attractive for the abundant application in many disciplines. To explore the practical application of TENG devices, we firstly reported a novel TENG based on the white sugar (WS-TENG) to harvest mechanical energy, and simultaneously, which can also serve as the self-powered humidity sensor due to the essential hydrophilic property of white sugar molecules. In this work, the polytetrafluoroethylene (PTFE) film and white sugar play the role of triboelectric parts. Moreover, the electrical output of WS-TENG involved in the short-circuit current ( Isc ) and open-circuit voltage ( Voc ) can get to 6.35 µA and 95.68 V, respectively. The fabricated WS-TENG has good long-term durability and reliability. According to the experimental results, the self-powered humidity sensor based on the WS-TENG can reflect the humidity change of the environment. The current research could effectively promote the practical application of TENG devices.